UNITED NATIONS COMMITTEE ON THE PEACEFUL USES OF OUTER SPACE (UNCOPUOS) DALAM UPAYA ANTISIPASI MILITERISASI DI LUAR ANGKASA - Meirizal, Ade; Prisca Lusiani, Putu; Nurhalizah, Sarah (Jurnal Ilmiah Hubungan Internasional Fajar, 2023)
This article describes the United Nations Commission on the Peaceful Uses of Outer Space (UNCOPUOS), an international form of cooperation under the auspices of the United Nations that aims to establish rules for military operations in outer space to maintain world peace. The purpose of this article is to explain how international cooperation is seen from the perspective of Neoliberalism Institutionalism, which believes in the role of institutions as mediators in the formation of cooperation between countries in the international system. Using descriptive narrative method, this article demonstrates that UNCOPUOS, established in 1959, has created various forms of international treaty law that regulate the procedures of activities in outer space and are able to prevent anarchy in outer space activities which in reality are often dominated by large countries such as US, China, Russia, Japan and the European Union. In addition, UNCOPUOS is also actively campaigning for the potential of outer space for humanitarian benefit through the Space2030 Agenda, so it is important that peace in the region should be maintained in order to not endorse the egos and interests of particular entities.